Book Review: Neoliberalization, Universities and the Public Intellectual: Species, Gender and Class and the Production of Knowledge. Fraser, H., & Taylor, N. 2016. - Yan, Sijin (Critical Studies in Teaching and Learning, 2023)
Review of: Neoliberalization, Universities and the Public Intellectual: Species, Gender and Class and the Production of Knowledge. Fraser, H., & Taylor, N. 2016.